"Men never cry": Teaching Mormon Manhood in the Church of Jesus Christ of Latter-day Saints. Issue 3 (3rd July 2017) - Sumerau, J. E.; Cragun, Ryan T.; Smith, Trina
ABSTRACT: We examine the ways Mormon leaders establish "what it means to be a man" for their followers. Based on content analysis of over 40 years of archival material, we analyze how Mormon leaders represent manhood as the ability to signify control over self and others as well as an inability to be controlled. Specifically, we demonstrate how these representations stress controlling the self, emotional and sexual expression, and others while emphasizing the development of self-reliance and independence from others' control. We draw out implications for understanding (1) how religious leaders create ideal notions of manhood, (2) what the religious interpretations of secular constructions of manhood are, and (3) how these relate to the reproduction of gender inequalities.